Transcriptional regulation of thorn tip sclerification in plants - Jie Ren; Yaoyuan Duan; Ruoqi Li; Xin Zhang; Yanfei Shi; Shiyun Zhou; Kaidong Xie; Xiaomeng Wu; Vivian F. Irish; Xiuxin Deng; Fei Zhang; Wenwu Guo (Proceedings of the National Academy of Sciences, 2025)
A common characteristic of thorns, prickles, and spines is a hardened and sharp tip. This feature complicates cultivation and postharvest processing for many crops, yet the molecular mechanisms governing this specific sclerification process remain unclear. By genome editing screening, we identified a MYB family gene named S HORT and S OFT T HORN 1 ( SST1 ) that specifically promotes the development of sclerenchyma cells at Citrus thorn tips. CRISPR-Cas9 editing of SST1 results in the formation of short and soft thorns with significantly reduced secondary wall thickening at the tips, while leaving stem growth unaffected. SST1 directly activates NST1 and SND1 , driving a hierarchical transcriptional regulatory network for secondary wall biosynthesis. Moreover, SST1 homologs in various species are specifically expressed in thorns, suggesting a potential conserved role. Our results uncover the molecular basis for hard plant protective structures, and modulation of this pathway could be an effective strategy for optimizing cultivation practices.